PCR-based identification of Trypanosoma lewisi and Trypanosoma musculi using maxicircle kinetoplast DNA - Hong, Xiao-Kun (2017)
Fil: Hong, Xiao-Kun. Sun Yat-Sen University. School of Life Sciences. State Key Laboratory of Biocontrol. Center for Parasitic Organisms, Cantón; China.